Diversidad y educación especial - Maritza Marín-Cabrera (Universidad Nacional, Costa Rica, 2007)
This article discusses diversity and special education, emphasizing the relevance of respect for equal opportunities as well as for values and attitudes within the school context. In spite of the fact that schools have improved in these aspects throughout the years, there is still lot of work to do in order to transform our schools in inclusive institutions. Special attention is given to people with Down Syndrome who are integrated to the Regular System; students with dreams and illusions who participate in different integrated programs providing an example of tenacity. Furthermore, several pre-school integration centers were visited and a lot of necessities of attention to the general population were detected. This article presents different methodological strategies designed to produce meaningful and functional learning processes, respecting student's diversity. Accordingly, this is a useful article to educators, especially those who work with pre-schooled children.